2013
DOI: 10.14233/ajchem.2013.f31
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Recyclability of Ionic Thermoplastic Rubber Based on Citraconated Ethylene Propylene Diene Monomer

Abstract: The mechanical properties and recyclability of novel ionomers based on citraconated ethylene propylene diene monomer (EPDM) were examined. Citraconated EPDM (CCA-g-EPDM) was synthesized using a melt grafting technique from citraconic acid (CCA)/EPDM/free radical initiator [2,5-dimethyl-2,5-di(tert-butyl peroxy) hexane: L-101]. Ionomers (IZnO(5), IZnO(10), IZnSt.( 5), IZnSt.(10), IZnO(5)/ZnSt.( 5)) based on citraconated EPDM were prepared by melt mixing from CCA-g-EPDM and zinc oxide and/or zinc stearate using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Citraconated EPDM (EPDM‐g‐CCA) was prepared by melt grafting from citraconic acid (CCA)/EPDM/free radical initiator [2,5‐dimethyl‐2,5‐di(tert‐butyl peroxy) hexane: L‐101] using Haake Rheocorder (Rheocord 9000, Haake Co., Germany) under 50 rpm, at 160°C for 15 min. The EPDM‐g‐CCA with 1.78% of percent grafting and 18.0% of gel content was prepared by free radical melt graft copolymerization of pristine EPDM (100 g) with citraconic acid (CCA, 2 g)/initiator (L‐101, 0.04 g) . Percent grafting (%) of EPDM‐g‐CCA was determined by the following equation: Percent grafting true(%true)=true[true(normalWnormalg Wnormalotrue)/normalWnormalotrue]×100 where the dry weights of EPDM‐g‐CCA extracted in acetone at 40°C for 48 h and pristine EPDM are W g and W o , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Citraconated EPDM (EPDM‐g‐CCA) was prepared by melt grafting from citraconic acid (CCA)/EPDM/free radical initiator [2,5‐dimethyl‐2,5‐di(tert‐butyl peroxy) hexane: L‐101] using Haake Rheocorder (Rheocord 9000, Haake Co., Germany) under 50 rpm, at 160°C for 15 min. The EPDM‐g‐CCA with 1.78% of percent grafting and 18.0% of gel content was prepared by free radical melt graft copolymerization of pristine EPDM (100 g) with citraconic acid (CCA, 2 g)/initiator (L‐101, 0.04 g) . Percent grafting (%) of EPDM‐g‐CCA was determined by the following equation: Percent grafting true(%true)=true[true(normalWnormalg Wnormalotrue)/normalWnormalotrue]×100 where the dry weights of EPDM‐g‐CCA extracted in acetone at 40°C for 48 h and pristine EPDM are W g and W o , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, understanding the effect of melt processing/recycling on the properties of citraconated EPDM‐based ionomers is very important for reusing. Our previous study examined citraconated EPDM (EPDM‐g‐CCA) and mechanical properties and recyclability of EPDM‐g‐CCA ionomers . We found that the mechanical properties and compression set (CS) resistance increased in the order of EPDM‐g‐CCA ionomers > EPDM‐g‐CCA > pristine EPDM.…”
Section: Introductionmentioning
confidence: 99%